Systematic review of the effectiveness of stage based interventions to promote smoking cessation. Issue 7400 (29th May 2003) - Riemsma, Robert Paul; Pattenden, Jill; Bridle, Christopher; Sowden, Amanda J; Mather, Lisa; Watt, Ian S; Walker, Anne
Abstract: Objective To evaluate the effectiveness of interventions using a stage based approach in bringing about positive changes in smoking behaviour. Design Systematic review. Data sources 35 electronic databases, catalogues, and internet resources (from inception to July 2002). Bibliographies of retrieved references were scanned for other relevant publications, and authors were contacted if necessary. Results 23 randomised controlled trials were reviewed; two reported details of an economic evaluation. Eight trials reported effects in favour of stage based interventions, three trials showed mixed results, and 12 trials found no statistically significant differences between a stage based intervention and a non-stage based intervention or no intervention. Eleven trials compared a stage based intervention with a non-stage based intervention, and one reported statistically significant effects in favour of the stage based intervention. Two studies reported mixed effects, and eight trials reported no statistically significant differences between groups. The methodological quality of the trials was mixed, and few reported any validation of the instrument used to assess participants' stage of change. Overall, the evidence suggests that stage based interventions are no more effective than non-stage based interventions or no intervention in changing smoking behaviour. Conclusions Limited evidence exists for the effectiveness of stage based interventions in changing smoking behaviour.